Current practice in the rehabilitation of complex regional pain syndrome: a survey of practitioners. Issue 7 (27th March 2019) - Miller, Caroline; Williams, Mark; Heine, Peter; Williamson, Esther; O'connell, Neil
Abstract: Introduction: International clinical guidelines for Complex Regional Pain Syndrome recommend a wide range and variation of rehabilitation therapies as the core treatment. It is likely that most therapists employ a range of approaches when managing people with Complex Regional Pain Syndrome but a recent Cochrane review identified little evidence relating to the effectiveness of multi-modal rehabilitation. There is need for up to date trials of rehabilitation for Complex Regional Pain Syndrome, but in order to develop a clear model of best practice that can be rigorously evaluated we need to understand current practice. Method: An electronic survey was disseminated internationally to clinicians involved in the rehabilitation of individuals with Complex Regional Pain Syndrome. The survey aimed to establish which criteria are used for diagnosis and which modalities clinicians use to treat Complex Regional Pain Syndrome and which they consider ineffective or harmful. Results: 132 valid responses were received. A third of participants did not use any established criteria to diagnose Complex Regional Pain Syndrome. Current practice commonly included patient education, encouragement of self-management, and physical exercises. Cortically directed treatments such as graded motor imagery and psychological approaches were often incorporated into treatment whereas pain provocative therapies, splinting, contrast bathing, and cold and heat therapy were rarely used in the acute or chronic phase of Complex Regional Pain Syndrome. Conclusion: A broad range of modalities are currently used in Complex Regional Pain Syndrome rehabilitation. Practice appears to be characterized by educational and exercise based interventions delivered in a pain-contingent manner which largely echoes recommendations in international clinical guidelines. Implications for Rehabilitation: Patients with Complex Regional Pain Syndrome suffer from a painful and disabling condition for which we still do not know the best treatment options. From our survey sample most clinicians use treatments recommended in the international guidelines. A large proportion of clinicians from our survey sample are not using internationally recognized diagnostic criteria and we therefore recommend that clinicians become familiar with these criteria and use them for all suspected Complex Regional Pain Syndrome cases.